Poor newborn care practices - a population based survey in eastern Uganda - Peterson Stefan; Waiswa Peter; Tomson Goran; Pariyo George W (BMC, 2010)
Abstract Background Four million neonatal deaths are estimated to occur each year and almost all in low income countries, especially among the poorest. There is a paucity of data on newborn health from sub-Saharan Africa and few studies have assessed inequity in uptake of newborn care practices. We assessed socioeconomic differences in use of newborn care practices in order to inform policy and programming in Uganda. Methods All mothers with infants aged 1-4 months (n = 414) in a Demographic Surveillance Site were interviewed. Households were stratified into quintiles of socioeconomic status (SES). Three composite outcomes (good neonatal feeding, good cord care, and optimal thermal care) were created by combining related individual practices from a list of twelve antenatal/essential newborn care practices. Multiple logistic regression analysis was used to identify determinants of each dichotomised composite outcome. Results There were low levels of coverage of newborn care practices among both the poorest and the least poor. SES and place of birth were not associated with any of the composite newborn care practices. Of newborns, 46% had a facility delivery and only 38% were judged to have had good cord care, 42% optimal thermal care, and 57% were considered to have had adequate neonatal feeding. Mothers were putting powder on the cord; using a bottle to feed the baby; and mixing/replacing breast milk with various substitutes. Multiparous mothers were less likely to have safe cord practices (OR 0.5, CI 0.3 - 0.9) as were mothers whose labour began at night (OR 0.6, CI 0.4 - 0.9). Conclusion Newborn care practices in this setting are low and do not differ much by socioeconomic group. Despite being established policy, most neonatal interventions are not reaching newborns, suggesting a "policy-to-practice gap". To improve newborn survival, newborn care should be integrated into the current maternal and child interventions, and should be implemented at both community and health facility level as part of a universal coverage strategy.